Different Outcomes in the Acquisition of Residual V2 and Do-Support in Three Norwegian-English Bilinguals: Cross-Linguistic Influence, Dominance and Structural Ambiguity - Anderssen, Merete; Bentzen, Kristine (Frontiers in Psychology, 2018)
This paper investigates the acquisition of residual verb second (V2) in three corpora consisting of data from Norwegian-English bilinguals (Emma, Emily and Sunniva) in order to determine to what extent these structures are affected by cross-linguistic influence (CLI) from Norwegian V2. The three girls exhibit three different patterns with regard to the relevant constructions. They are very target-like in their use of auxiliaries in the relevant structures. However, when it comes to do-support, Emily and Sunniva are equally target-like, while Emma mainly produces non-target-like structures. These either involve the omission of do, or non-target-like movement of a lexical verb. Furthermore, Emma also allows verb movement across the subject with both lexical verbs and auxiliaries in topicalised structures, suggesting that she has overgeneralised residual V2 across verb types and clause types. Emily, on the other hand, is very target-like in structures involving residual V2 in English, but also allows auxiliaries and dummy-do to move across the subject in topicalised structures, overgeneralising residual V2 to apply to non-subject-initial declaratives. Finally, Sunniva is very precocious and very target-like in all the relevant structures, which may be an indication of acceleration due to CLI from Norwegian V2. We discuss these results with reference to language balance, finding that the measures available to us suggest that the differences between the children cannot straightforwardly be explained by language dominance. Instead, we suggest that these results can be accounted for by ambiguity in the English system, leaving the data open to several possible interpretations when acquired in contact with the consistent V2 system in Norwegian. This has several consequences: (i) the three girls’ parsers interpret the input differently, (ii) differences between the three children are qualitative rather than quantitative and (iii) there has to be some mechanism that ensures that the children can ‘recover’ from these non-target-like grammars. In this paper, we will focus on the first two issues.